Sosialisasi Kewirausahaan Pemberdayaan Ekonomi Masyarakat Pada Warga Jalan Pulai Payung RT.12 RW.04 Keluran Surabaya Kecamatan Sungai Serut Kota Bengkulu - Wagini, Wagini; Gayatri, Ida Ayu Made Er Meytha; Irwanto, Tito; Melinda, Tri Febrina; Indriasari, Nia (Jurnal Dehasen Mengabdi, 2022)
Entrepreneurship is the first step for mothers to develop their own abilities to help the family economy, with the entrepreneurial spirit of the residents of Jalan Pulai Payung RT.12 RW. 04. The Surabaya sub-district, Sungai Serut sub-district, Bengkulu City has a very broad positive impact, including being able to channel the talents that exist in each of them, being able to find out what kind of products the market wants, and being able to find out a good market share for the products that are produced both in terms of appearance. from the place and the way of marketing. With this entrepreneurship socialization, it can solve the problems faced by women residents of Jalan Pulai Payung RT.12 RW. 04. Surabaya sub-district, Sungai Serut sub-district, Bengkulu City, to awaken the entrepreneurial spirit in each of them, and to be able to practice what skills are possessed by mothers. In this case, the ability possessed by the majority of mothers is in making tat cakes. Entrepreneurship socialization carried out in this service is carried out in several stages, the first stage is awareness, the second stage is capacity building and the last stage is the empowerment stage. 04. Surabaya sub-district, Sungai Serut sub-district, Bengkulu City and can be received with quite high enthusiasm. After the entrepreneurship socialization was carried out, the mothers immediately put it into practice together. The most important thing in this case is the emergence of the soul of the mothers to be able to develop themselves together in this case, making cakes and selling to the market and following current technological advances. It is hoped that every mother can use her time in a useful way and can help to improve the economy of the families of the residents of Jalan Pulai Payung RT. 12 RW. 04. Surabaya village, Sungai Serut sub-district, Bengkulu city.